2011
DOI: 10.1177/1533317511411177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Motor and Multisensory-Based Approach on Residents with Moderate-to-Severe Dementia

Abstract: Involving institutionalized people with dementia in their routines may be challenging, particularly in advanced stages of the disease. Motor and multisensory stimulation may help to maintain or improve residents' remaining abilities such as communication and self-care. This study examines the effects of a motor and multisensory-based approach on the behavior of 6 residents with moderate-to-severe dementia. A single-group, pre- and post test design was conducted. Motor and multisensory stimulation strategies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 45 publications
1
64
0
Order By: Relevance
“…Four out of the five that reported communication outcomes found post-training improvements in communication and interaction (Alnes et al, 2011;Galvin et al, 2010;Robinson et al, 2010;Weitzel et al, 2011). One small study found a nonsignificant trend towards improved communication (Cruz et al, 2011). All four studies that reported knowledge outcomes found improvements post-training (Beer et al, 2012;Bray et al, 2015;Galvin et al, 2010;Velzke, 2014).…”
Section: Residential Care and Hospital Settingsmentioning
confidence: 95%
See 1 more Smart Citation
“…Four out of the five that reported communication outcomes found post-training improvements in communication and interaction (Alnes et al, 2011;Galvin et al, 2010;Robinson et al, 2010;Weitzel et al, 2011). One small study found a nonsignificant trend towards improved communication (Cruz et al, 2011). All four studies that reported knowledge outcomes found improvements post-training (Beer et al, 2012;Bray et al, 2015;Galvin et al, 2010;Velzke, 2014).…”
Section: Residential Care and Hospital Settingsmentioning
confidence: 95%
“…Four studies were clearly protocol driven and provided enough information to conclude a low risk of reporting bias (Chenoweth et al, 2014;CristanchoLacroix et al, 2015;Livingston et al, 2013;Orgeta et al, 2015). Ten studies reported small sample sizes (Alnes, Kirkevold, & Skovdahl, 2011;Beer, Hutchinson, & Skala-Cordes, 2012;Cristancho-Lacroix et al, 2015;Cruz, Marques, Barbosa, Figueiredo, & Sousa, 2011;Gentry, 2011;Haberstroh et al, 2011;Liddle et al, 2012;Prick et al, 2015;Raglio et al, 2016;van der Ploeg et al, 2013). Eight studies used unstandardised measures (Alnes et al, 2011;Bray et al, 2015;Broughton et al, 2011;Galvin et al, 2010;Judge, Yarry, Orsulic-Jeras, & Piercy, 2010;Robinson, Bamford, Briel, Spencer, & Whitty, 2010;Velzke, 2014;Weitzel et al, 2011); therefore it is not clear if these are reliable and valid and it is difficult to compare outcomes between studies.…”
Section: Quantitative Studiesmentioning
confidence: 99%
“…It has been recommended that, in the middle to late stages of the disease, the activities should focus on fine-and gross-motor and sensory activities 2,7,10 . Consistent with this recommendation, there are currently two main approaches with promising results in people with moderate to severe dementia: Multisensory Stimulation and Motor Stimulation [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 88%
“…By stimulating the senses in a format that can be understood by the individual, it is expected that people with dementia will respond appropriately to their surroundings and communicate with others 18 , for example, by giving a smile or thanking to the caregiver 15 . MSS has been found to reduce the frequency of behavior problems and apathy 14,16 , improve communication 7,19 and functional performance 20 and increase residents' attentiveness 12,21 . Motor stimulation (MS) aims to maintain or improve, as long as possible, the remaining physical abilities of people with dementia 12,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation